Validation of the Group Environment Questionnaire (GEQ) in a Simulated Learning Environment - José Manuel García-Álvarez; Alfonso García-Sánchez; Alonso Molina-Rodríguez; María Suárez-Cortés; José Luis Díaz-Agea (Nursing Reports)
Background/Objectives: The complexity of modern healthcare requires teamwork. Healthcare teams must be cohesive to ensure efficient and quality care. The objective of this study was to validate the Spanish short version of the Group Environment Questionnaire (GEQ) in undergraduate nursing students undergoing clinical simulation training. Methods: The psychometric properties of the questionnaire were analyzed. We began with a statistical analysis of the items. Internal consistency was assessed using McDonald’s omega coefficient. Test-retest reliability was determined using Spearman’s correlation coefficient. An exploratory factor analysis was performed using the principal components analysis method with varimax rotation. Finally, a confirmatory factor analysis of the proposed theoretical models was performed to select the most appropriate one using the weighted least squares method adjusted for mean and variance (WLSMV) and goodness-of-fit indices. Results: The questionnaire items showed a standard deviation higher than 1 and a negative skewness lower than 0.5. Internal consistency and test-retest reliability were higher than 0.8. The item-total correlation coefficient values were above 0.44. The exploratory factor analysis confirmed the presence of four factors, each with three items. Confirmatory factor analysis determined that the four-factor cohesion model was the one that obtained the best fit. Conclusions: The Spanish short version of the Group Environment Questionnaire (GEQ) is a valid and reliable instrument for analyzing group cohesion in teams of nursing students undergoing clinical simulation training.